Weight Loss and Sexual Activity in adult Obese Individuals: Establishing a Causal Link - Harald Tauchmann; Arndt Rüdiger Reichert; Ansgar Wübker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Obesity may not only be linked to undesirable health outcomes but also to limitations in sexual life. The present paper aims to assess whether there is a relationship between weight change and sexual activity in obese individuals. To address the endogeneity of weight loss that is likely to result in biased estimation results, the analysis is based on data from a randomized controlled trial. In this experiment financial weight-loss rewards were randomly offen and to a subgroup of participants and can be used as exogenous source of weight variation in an instrumental variables approach. Estimation results indicate that for obese males loosing weight increases both the probability for being involved in a sexual relationship. Conditional on having already lost some weight, a further reduction of obesity also increases the frequency of sexual intercourse.
Keywords: I12; J12; J13; 330